The Peer Model Advantage in Infants’ Imitation of Familiar Gestures Performed by Differently Aged Models - Zmyj, Norbert; Aschersleben, Gisa; Prinz, Wolfgang; Daum, Moritz (Frontiers in Psychology, 2012)
Research on infant´s imitation of differently aged models, which has predominantly studied object- related actions, has so far lead to mixed evidence. Whereas some studies reported an increased likelihood of imitating peer models in contrast to adult models, other studies reported the opposite pattern of results. In the present study, 14-month-old infants were presented with four familiar gestures (e.g., clapping) that were demonstrated by differently aged televised models (peer, older child, adult). Results revealed that infants were more likely to imitate the peer model than the older child or the adult. This result is discussed with respect to a social function of imitation and the cognitive mechanism of imitating familiar behavior.